Modelo de gestión administrativa basada en Balanced Scorecard en la compañía de transporte de turismo Cottullari S.A. - Espín Riofrio, Marianela Alexandra (2022)
The strategic performance of organizations is frequently derived from the conception of its administrative management and its structure for its functionality, which constitutes a strategic element that proposes deployment in all areas for its performance and the use of available resources and so on. relate the application of a versatile tool to turn it into business information. The objective of the research is to design an administrative management model based on Balanced Scorecard in order to improve the performance of the tourism transport company Cottullari S.A. taking into consideration the most relevant factors for the success of its administration. The research has a qualitative approach of a descriptive type with a systematic process, and a basic modality of an exploratory nature with data collection techniques such as direct observation and the application of a logical structure that seeks to integrate the areas involved. The results of this measurement and administration system indicate the need for the company to integrate into the competitive environment through action strategies focused on the objectives with the application of corporate strategies that imply a change in organizational culture. The conclusions express the resulting effectiveness for the company and the responsibility to respond to the presence of weaknesses related to the integration of areas despite the creation of long-term value that supports the operational development of internal management, representing a limitation to specify strategic plans and actions in their context.